The Effects of the Pancasila Student Profile Strengthening Project on the Mutual Cooperative Attitude of Students at SMP Negeri 8 Purwokerto - Lestari, Ega; Priyanto, Eko; Sadeli, Elly Hasan (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine the effects of the Pancasila Student Profile Strengthening Project on the mutual cooperative attitude of students at SMP Negeri 8 Purwokerto. The research method used in this study is descriptive analysis with a quantitative approach. The population in this study consists of seventh and eighth-grade students at SMP Negeri 8 Purwokerto. The sample size is 237 students, determined using a simple random sampling technique. Data collection techniques employed in this study include questionnaires, observations, interviews, and documentation. The research findings indicate a positive and significant impact of the Pancasila Student Profile Strengthening Project on the mutual cooperative attitude of students at SMP Negeri 8 Purwokerto. The influence of the Pancasila Student Profile Strengthening Project on students’ mutual cooperative attitudes is measured at 0.376, which can be interpreted as the independent variable (X) - the Pancasila Student Profile Strengthening Project - contributing 37.6% to the dependent variable (Y) mutual cooperative attitude. This can be seen in the students’ mindset, which fosters collaboration and teamwork, social sensitivity and concern, and a sharing attitude.